Analisis Kompetensi Dan Perilaku Kerja Inovatif Terhadap Kinerja Pegawai Yang Dimediasi Knowledge Sharing - Nurchalis Matdoan; Nasharuddin Mas; Choirul Anam (Jurnal Manajemen Kreatif dan Inovasi, 2024)
The purpose of this research is to empirically determine the analysis of competency and innovative work behavior on employee performance mediated by knowledge sharing by conducting a study at the Tual City Personnel and Human Resource Development Agency). This research is positivism research, with the type of research being explanatory research. The population in this study was all employees of the Tual City Personnel and Human Resource Development Agency, totaling 33 people. The data analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS application. The research results show that competency is empirically unable to encourage increased employee performance. Innovative work behavior is empirically unable to encourage increased employee performance. Competency can empirically encourage increased knowledge sharing. Innovative work behavior is empirically able to encourage increased knowledge sharing. Knowledge sharing is empirically able to encourage increased employee performance. Competency is empirically able to encourage increased employee performance mediated by knowledge sharing. Innovative work behavior is empirically able to encourage increased employee performance mediated by knowledge sharing.